Literasi Pengembangan Produk Umkm Berbasis Kelor Sebagai Solusi Ekonomi Kreatif Dan Ketahanan Pangan Masyarakat Umkm Dapur Aru - Rahmawati, Rahmawati; Assyifa, Zubaidah; Hasda, Mifta; Amelia, Nur; Amalia, Nala (EL-EMIR INSTITUTE, 2025)
This community service activity was aimed at the Dapur Aru MSME community as a solution to support the creative economy and food security through the development of moringa-based products. The main objective was to provide understanding of the literacy involved in developing MSME products based on moringa. The methods used included counseling, presentations, discussions, Q&A sessions, and practical exercises. The counseling explained the importance of moringa product innovation, the presentations outlined the product literacy process, the Q&A sessions offered opportunities for consultation, and the practical exercises assessed participants' understanding before and after the material was delivered. The success of this activity was supported by the availability of experts, participant enthusiasm, and the support of the community leader. However, challenges included limited human resources, production capacity, and lack of skills in business management, hygienic and efficient production processes, quality control, and product development. The results showed that the program ran smoothly according to plan. Most participants understood moringa literacy well, although further support is needed in technical business aspects. All activities were carried out on schedule and according to plan through strong collaboration.